Variation of Isoprenoid GDGTs in the Stratified Marine Water Column: Implications for GDGT-Based TEX86 Paleothermometry - Guo, Jinqiang; Yuan, Huamao; Song, Jinming; Qu, Baoxiao; Xing, Jianwei; Wang, Qidong; Li, Xuegang; Duan, Liqin; Li, Ning; Wang, Yingxia (Frontiers in Marine Science, 2021)
Isoprenoid glycerol dialkyl glycerol tetraethers (isoGDGTs) derived from archaea are lipid biomarkers that exhibit high sensitivity to changes in water temperature, leading to the widespread application of the isoGDGT-based tetraether index of 86 carbon atoms (TEX86) in surface seawater temperature (SST) reconstruction. However, there remain some uncertainties regarding the robustness of TEX86 under changing water conditions (e.g., variations in water depth, oxygen and pH). Here, we analyzed isoGDGTs in suspended particles at different depths of the East China Sea (ECS) during summer 2020, aiming to constrain the applicability of the TEX86 proxy in coastal waters. Our data showed that the isoGDGTs were mainly derived from planktonic Thaumarchaeota, as revealed by the low ratio of GDGT-0/crenarchaeol (<0.5). The vertical distribution of isoGDGT concentration depicted a downward increase from the surface to the bottom. This observation was likely shaped by Thaumarchaeota, which regulate the extent of ammonia oxidation based on the availability of ammonium. The occurrence of maximal isoGDGT concentrations in the bottom layer suggests that the isoGDGTs in sediments are mainly controlled by bottom archaeal production rather than surface archaeal production. By reanalyzing the published isoGDGT data of surface sediments in the ECS inner shelf, we found that the sedimentary TEX86 relates much better to the annual mean bottom seawater temperature (BST) than to the annual mean SST, indicating that sedimentary TEX86 is more inclined to be a proxy for the BST in the shallow ECS. In addition, the positive bias of TEX86 driven by low dissolved oxygen and low pH was observed under the pycnocline, indicating that the application of TEX86 to reconstruct seawater temperature should be carefully appraised in coastal environments with strong water column stratification.